Financial reforms and balance-of-payments crisis the case of the Philippines : 1980-83 - Remolona, Eli M. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1986)
In the Philippines, financial reforms began in earnest in July 1981 with the deregulation of bank interest rates. But within two years, a crisis in the balance-of-payments intervened. This paper addresses two major issues. First, to what extent did the financial reforms contribute to the balance-of-payments crisis? The findings indicate that while the reforms do seem to have made it more difficult to finance the budget deficits in 1981 to 1982, they did so only in a minor way. Given the enormity of the budget deficits and the rate at which foreign exchange reserves were depleted, it does not look as if the balance-of-payments crisis would have been prevented had the reforms not been introduced. The second issue is: To what extent did the reforms weaken the financial sector's ability to weather the external crisis. The findings show that the sudden increase in deposit rates in 1981 and 1982 while the interest rates on outstanding loans remained the same hurt many banks. Even the increase in the interest rate on new loans contracted in 1984 was not enough to compensate for the interest rate loss incurred on medium- and long-term loans contracted in the previous years. Indeed, this has severely weakened the banking system's ability to weather the balance-of-payments crisis.